Stress Response Simulated by Continuous Injection of ACTH Attenuates Lipopolysaccharide-Induced Inflammation in Porcine Adrenal Gland - Sun, Zhiyuan; Cai, Demin; Yang, Xiaojing; Shang, Yueli; Li, Xian; Jia, Yimin; Yin, Chao; Zou, Huafeng; Xu, Yunming; Sun, Qinwei; Zhang, Xuhui (Frontiers in Veterinary Science, 2020)
In modern farms animals are at high risks of bacterial invasion due to environmental stress factors. The adrenal gland is the terminal organ of stress response. The crosstalk between adrenal endocrine stress and innate immune response is critical for the maintenance of immune homeostasis during inflammation. Thus, it’s important to explore whether stresses play a pivotal role in lipopolysaccharide (LPS)-induced inflammatory response in porcine adrenal gland. 30-day-old Duroc × Landrace × Large White crossbred piglets (12 ± 0.5 kg) were randomly allocated into 4 groups in a 2 × 2 factorial arrangement of treatments, including ACTH pretreatment (with or without ACTH injection) and LPS challenge (with or without LPS injection). Each group consisted of 6 male piglets. The results showed that our LPS preparation alone induced mRNA expressions of IL-1β, IL-6, TNF-α, IL-10, COX-2, TLR2, TLR4, and GR (P<0.05). ACTH pretreatment down-regulated TLR2 mRNA and IL-6 protein level induced by our LPS preparation significantly (P<0.05) by One-way ANOVA analysis. Treatment with LPS alone extremely significantly decreased ssc-miR-338 level (P<0.01). Interaction of ACTH×LPS was significant for cNOS level (P=0.011) and ssc-miR-338 expression (P=0.04) by Two-way ANOVA analysis. The LPS treatment significantly down-regulated cNOS level (P<0.01), which was significantly attenuated by ACTH pretreatment (P<0.05). Lipopolysaccharide alone did not affect ssc-miR-146b expression level compared to that in vehicle group. However, ACTH pretreatment in combination with LPS significantly increased this micro-RNA expression (P<0.05). TLRs 1-10 were all expressed in adrenal tissue. The LPS challenge alone induced remarkable compensatory mitochondrial damages at the ultrastructural level, which was alleviated by ACTH pretreatment. Accordingly, ACTH pretreatment was able to block LPS-induced secretion of local adrenal cortisol (P<0.05). Taken together, our results demonstrate that ACTH pretreatment seems to attenuate LPS-induced mitochondria damage and infammation that decreased cNOS activity in adrenal gland, and ultimately returned local adrenal cortisol to basal levels at 6 h post LPS injection.